Carabid beetles (Coleoptera: Carabidae) in coniferous plantations in Hokkaido, Japan: effects of tree species and environmental factors. Issue 2 (1st August 2014) - Kaizuka, Jun; Iwasa, Mitsuhiro
Abstract The distribution, species composition and abundance of carabid beetles in monospecific plantations of three different coniferous tree species (Japanese spruce, Sakhalin fir and larch) were investigated by baited pitfall traps in Hokkaido, Japan. In total, 16 150 carabid beetles consisting of 31 species in 13 genera were collected in 2011 and 2012. The most predominant species was Pterostichus thunbergii Morawitz, followed by Synuchus melantho (Bates) and Carabus opaculus (Putzeys). Average numbers of beetles per trap were significantly reduced in larch. Large‐sized Carabus species (C. arboreus arboreus Lewis and C. opaculus) were collected in large numbers in Japanese spruce. There was no significant difference in diversity and equitability among the three kinds of plantation. The ordination of redundancy analysis showed that medium‐sized forest generalists, Pterosticus subovatus (Motschulsky) and P. thunbergii, were highly associated with Japanese spruce and Sakhalin fir, and the forest specialist Synuchus nitidus (Motschulsky) was with Sakhalin fir. In contrast, in larch there was no such associated forest species, and some species of Carabus, Pterostichus and Synuchus were considerably reduced in number, suggesting that larch has unfavorable effects on some forest species. The most important environmental variables influencing carabid assemblages were soil moisture and foliage layer cover. Practices in forest management to minimize the effects of plantations on carabid assemblages are discussed.